Public Space and Women: A Case Study of Mosque Friendliness Towards Women in Ambon City - Muhajir Abd. Rahman; Sugi, La; Wa Rosita Wally; Siti Mutmainnah (IAIN Ambon, 2024)
Changing times require women to do outdoor activities, so women must look for alternatives to carry out their worship comfortably. However, what happens is that there are still many mosques as public spaces that are not friendly to the presence of women, both in terms of infrastructure and service facilities. This research uses a qualitative approach with a case study method, taking the research location in Ambon City. Ambon was chosen as the research location because it is the centre of the Maluku community's government, education, and economy, with a population of 1,031,587 Muslims. The research results found that many mosques in Ambon City were unfriendly and exclusive for women. This mosque's lack of friendliness is caused by several factors, namely the mosque planning process that does not involve women, men dominating the mosque too much, and there is still a negative stigma towards women who do activities outside the home. To be able to realize a mosque as a public space that is friendly and accessible to all groups requires efforts from all parties.